Chromodynamical analysis of lenticular galaxies using globular clusters and planetary nebulae - Zanatta, Emilio J.B.; Cortesi, Arianna; Chies-Santos, Ana L.; Forbes, Duncan A.; Romanowsky, Aaron J.; Alabi, Adebusola B.; Coccato, Lodovico; Mendes de Oliveira, Claudia; Brodie, Jean P.; Merrifield, Michael (Oxford University Press, 2018)
Recovering the origins of lenticular galaxies can shed light on the understanding of galaxy formation and evolution, since they present properties that can be found in both elliptical and spiral galaxies. In this work we study the kinematics of the globular cluster (GC) systems of three lenticular galaxies located in low density environments (NGC2768, NGC3115 and NGC7457), and compare them with the kinematics of planetary nebulae (PNe). The PNe and GC data come from the Planetary Nebulae Spectrograph and the SLUGGS Surveys. Through photometric spheroid-disc decomposition and PNe kinematics we find the probability for a given GC to belong to either the spheroid or the disc of its host galaxy or be rejected from the model. We find that there is no correlation between the components that the GCs are likely to belong to and their colours. Particularly, for NGC2768 we find that its red GCs display rotation preferentially at inner radii (Re < 1). In the case of the GC system of NGC3115 we find a group of GCs with similar kinematics that are not likely to belong to neither its spheroid nor disc. For NGC7457 we find that 70% of its GCs are likely to belong to the disc. Overall, our results suggest that these galaxies assembled into S0s through different evolutionary paths. Mergers seem to have been very important for NGC2768 and NGC3115 while NGC7457 is more likely to have experienced secular evolution.